Pelatihan Pembuatan Pupuk Organik Cair Dengan Bantuan Lalat Hitam (Black Soldier Fly) Di Desa Sumberjo Kabupaten Nganjuk - Junaidi Junaidi; Nina Lysanti; Nur Ulfa Turohmah; Nugraheni Hadiyanti (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
Management of organic and inorganic waste is carried out in an integrated and sustainable manner to overcome its negative impact on the environment. Processing organic waste into liquid organic fertilizer (POC) is one of the efforts to overcome waste problems and provide added value for the community. Household organic waste processing can be done with the help of black soldier fly (BSF) larvae so the processing is fast and efficient. Black soldier flies are potential organisms that function as decomposers of organic waste. This community service activity has been carried out in Sumberjo Village, Gondang District, Nganjuk Regency. The purpose of this activity is socialization and training on the manufacture of POC from household organic waste with the help of black soldier fly. The series of activities carried out are coordination and outreach to partner communities, production of liquid organic fertilizer processing equipment, training on making liquid organic fertilizer, and evaluation of community service activities. The people of Depok Hamlet, Sumberjo Village, Gondang District, and Nganjuk Regency welcome the activity of utilizing household organic waste. Socialization and training in making POC went well and smoothly. The community is quite understanding and interested in making liquid organic fertilizer. This activity provides direct benefits for the community regarding the innovation of making POC from household organic waste with the help of black flies and strengthening partnerships between higher education institutions and the community.